Analisis Karakteristik Literasi Generasi Alpha Dan Implikasinya Terhadap Layanan Perpustakaan - Rusmiatiningsih Rusmiatiningsih; Okky Rizkyantha (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The alpha generation has creative, passionate, dynamic, leadership, and confident characters in making future career decisions, inseparable from technology in completing their work. Technological developments and pandemic conditions drastically changed the values and concepts of the line of education in carrying out teaching and learning activities and in the transfer of information. In library services, for example, major changes are needed in managing and disseminating information to respond to these conditions. This is to provide a balance in adjusting the style and character of the alpha generation in obtaining information. The purpose of this study is to analyze the character of the alpha generation so as to find patterns of information needs. In addition, it aims to determine the implications for library services. In this study, the study used was a literature study. From the description of the analysis that has been carried out, it can be concluded that the alpha generation is a multitasking generation, digital native, does not like rules, is creative, and flexible, connects, and collaborates as well as practicum. While the context of the information needs of the alpha generation tends towards information in digital formats and direct, applicable and easy information to be directly shared through social media. The implications of library services are expected to adjust the pattern of service performance to meet the information needs of the alpha generation including: changes in expectations of access to library information services that focus on idealistic and fast and sophisticated personal convenience, readiness for data appearance that is ready to share or share data directly, use of social media for promotion and communication lines across generations, the competence of librarians as professional data analysts is not only managing and maintaining but also participating in generating and repackaging information.